Parental involvement and inclusive contexts - Felizardo, Sara (2017)
Parental involvement is a multifaceted concept that encompasses different contexts and can be presented in various formats. Within the inclusive approach, the collaborative model and partnership of parental involvement provides a frame of reference that can help support professionals, educators and teachers in their contacts with parents of children with disabilities. This study aims to analyze the relationships between the perspectives of parents and teachers of regular education and special education, about parental involvement in school. In this research we constitute two samples, one for parents or caregivers and other of special education teachers, formed respectively by 256 parents of children with and without disabilities and 107 teachers of school clusters that allowed the access to most participant´s research. The data were collected in six clusters of schools and also in APPDA (Portuguese Association for Developmental Disorders and Autism) and APCV (Cerebral Palsy Association in Viseu) of the district Viseu, as well as in other places of the same district. The comparative analysis of perceptions of parental involvement between parents and teachers, data shows that the largest divergence occurs between the regular education teachers and parents of students with disabilities. In contrast, the perceptions between special education teachers and parents of children with disabilities do not show significant differences. There are still significant differences between the two types of teachers (regular and special education) about perceptions of parental involvement.